An explorative study of workplace violence against nurses who care for older people - El‐Hneiti, Mamdouh (Nurs Open, 2019)
AIM: To explore the prevalence of workplace violence among nurses who care for older people and its association with working stress, job satisfaction and quality of care in Jordan. DESIGN: A cross‐sectional design was used. METHODS: A cluster random sampling was used to select three public hospitals, three private hospitals and 17 healthcare centres in Amman, Jordan. The researcher used a convenience sampling method to select 485 nurses. Data were collected between 2015–2016. RESULTS: Almost 60% of the participants have been victims of violence at the workplace during the past year. Nurses who consider violence a problem at work have high levels of working stress (p < .01) as well as lower levels of quality of care (p < .01) and job satisfaction (p < .001).